TEACHERS’ PERCEPTION ON THE IMPACT OF USING FIRST LANGUAGE TOWARDS ENGLISH CLASSROOM - Hilda Adelina Alfi (J-Shelves of Indragiri (JSI), 2023)
The investigation of teachers' viewpoints on non-native English-speaking students is the main topic of this study. Nevertheless, there is still uncertainty regarding the efficacy of implementing first language instruction in English classrooms. The purpose of this study is to better understand the viewpoints of instructors on the usage of native tongues in English classrooms. The research methodology included qualitative data collection, with the objective of acquiring a broad spectrum of information. The English teachers at Santi Witya Serong School in South Thailand are the study's participants. The findings shows that teacher was sometimes using Thai language as an instruction in English classroom but most of the instruction is on English as their targeted language. The results demonstrate that teachers noted that first language implementation increased students' desire to learn English, gave them a chance to better understand challenging concepts in the language, and inspired them to ask bold questions that clarify linguistic elements. In an English-speaking classroom, student interaction and communication can become quite difficult, particularly when there is a tendency for the students to have poor English language skills. Using the first language in the target language classroom can increase students' enthusiasm and eagerness to study regardless of their background level and can be seen as a sign of respect for those who still require help learning English. It is noteworthy that although having a classroom where all of the language used is English is good for the students, it is also vital to pay attention to the state of the students.